Determinación de los parámetros óptimos para la elaboración de conservas de pimiento del piquillo soasado. - Vértiz Vereau, Liliana Milagros (2012)
This research paper entitled “DETERMINATION OF THE IDEAL PARAMETERS FOR THE PRODUCTION OF CONSERVES OF PEPPER OF THE ROASTED PIQUILLO” uses the technology of combined methods by varying parameters such as time, temperature, pressure and concentration possible to ensure, maintain and enhance the organoleptic properties of the final product (canned piquillo peppers soasado) through a combination of barriers that ensure stability and quality. The aim of this thesis was to apply this technology in the control points of the development and preservation of pepper, and analyze the quality and lifespan of the products obtained. The preparation of the preserves are made as follows: the vegetable was selected, baked and then washed. Once this stage is packed with the packing, consisting of acids and salts in different concentrations. Analyses were performed both in the material fresh and processed products were moisture, pH, ° Brix and total acidity. For products already processed are made the same control. The results indicate that the combined application of the methods allows to preserve the products made at different temperatures and frequencies in the oven, different types of solutions and concentrations in the preparation of liquid of different pressures to the respective times in the exhauster and finally for validating the sample against temporary storage.